The Influence of TAP MPR's Position on The Hierarchy System of Indonesian Laws and Regulations - Gustama, Briliant; Al-Fatih, Sholahuddin; Sarita (Indonesia Law Reform Journal, 2022)
This study aims to analyze the influence of TAP MPR in Indonesia. Placement of MPR Provisions in Law No. 12 of 2011 on the hierarchy of Legislation in Indonesia becomes one of the problematics that needs to be discussed, on the grounds of the position of MPR provisions that are under exactly the Constitution of 1945. This is based on the position of the MPR Decree itself which will automatically become a reference to the rules under it, in accordance with the theory of stairs put forward by Hans Kelsen. Although from the point of view of the position of MPR determination is still understandable if Hans Nawiasky theory is used as the basis. But in terms of testing itself of course this will raise a big question mark for all of us because in the Constitution of 1945 institutions or institutions that have the right to conduct a test of the Law is the Constitutional Court and the Supreme Court, but within its own scope the Provision of MPR is outside the juridical territory of the two Institutions themselves. Therefore, there needs to be a solution if at any time the MPR Decree is not in accordance with the basis of the 1945 Constitution so that there will be no defects in one of the legal sources of the State of Indonesia. Abstrak Kajian ini bertujuan untuk menganalisis pengaruh TAP MPR di Indonesia. Penempatan Ketentuan MPR dalam Undang-Undang Nomor 12 Tahun 2011 tentang Hierarki Peraturan Perundang-undangan di Indonesia menjadi salah satu problematika yang perlu dibahas, dengan alasan kedudukan ketetapan MPR yang berada di bawah UUD 1945. Hal ini berdasarkan posisi Ketetapan MPR sendiri yang secara otomatis akan menjadi acuan aturan di bawahnya, sesuai dengan teori tangga yang dikemukakan oleh Hans Kelsen. Meski dari sudut pandang posisi penentuan MPR masih bisa dimaklumi jika teori Hans Nawiasky dijadikan dasar. Namun dalam hal pengujian sendiri tentunya hal ini akan menimbulkan tanda tanya besar bagi kita semua karena dalam UUD 1945 lembaga atau lembaga yang berhak melakukan uji materi UU adalah Mahkamah Konstitusi dan Mahkamah Agung, namun dalam lingkupnya sendiri Ketentuan MPR berada di luar wilayah yuridis kedua Lembaga itu sendiri. Oleh karena itu, perlu ada solusi jika sewaktu-waktu Ketetapan MPR tidak sesuai dengan dasar UUD 1945 sehingga tidak akan terjadi cacat pada salah satu sumber hukum Negara Indonesia.